Micronutrient and amino acid losses in acute renal replacement therapy. Issue 6 (November 2015) - Oh, Weng C.; Gardner, David S.; Devonald, Mark A.J.
Abstract : Purpose of review: A wide range of renal replacement therapies is now available to support patients with acute kidney injury. These treatments utilize diffusion, convection or a combination of these mechanisms to remove metabolic waste products from the bloodstream. It is inevitable that physiologically important substances including micronutrients will also be removed. Here we review current knowledge of the extent of micronutrient loss, how it varies between treatment modalities and its clinical significance. Recent findings: Very few studies have specifically investigated micronutrient loss in renal replacement therapy for acute kidney injury. Recent data suggest that trace elements and amino acids are lost during intermittent dialysis, hybrid therapies such as sustained low-efficiency diafiltration and continuous therapies. Extent of micronutrient loss appears to vary with treatment type, with continuous convection-based treatments probably causing greatest losses. Summary: Patients with acute kidney injury are at high risk of disease-related malnutrition. The use of renal replacement therapy, although often essential for life support, results in loss of micronutrients into the filtrate or dialysate. Losses are probably greater with continuous convective treatments, but it is not yet known whether these losses are clinically significant or whether their replacement would improve patient outcomes.